Correlation of CBD/CHD angulation with recurrent cholangitis in patients treated with ERCP - Chong, Charing CN; Chiu, Philip WY; Tan, Teresa; Teoh, Anthony YB; Lee, Kit Fai; Ng, Enders Kwok Wai; Lai, Paul BS; Lau, James YW (Endoscopy International Open, 2016)
Background and study aims: Endoscopic retrograde cholangiopancreatography (ERCP) with endoscopic sphincterotomy (EST) for bile duct stone extraction has a major role in the treatment of cholangitis. It is well known that certain risk factors predispose to recurrence of such stones. The aims of this study were to evaluate the correlation between angulation of the common bile duct (CBD), right hepatic duct (RHD), and left hepatic duct (LHD) with recurrent cholangitic attacks and to elucidate other risk factors that may be associated with these attacks.Patients and Methods: This is retrospective study included 62 patients who had undergone therapeutic endoscopic retrograde cholangiopancreatography (ERCP) for bile duct stones. Their medical records were followed until May 1, 2009. The RHD, LHD, and CBD angulation and CBD diameter were measured on cholangiography prior to any endoscopic procedures.Results: Among these 62 patients, 6 (9.7 %) had recurrence of cholangitis. Both angles of the RHD and the CBD were significantly smaller in the group with recurrence (P = 0.001, P = 0.004). A CBD angle ≤ 130o and RHD angle ≤ 125o were found to be significantly associated with an increased risk of recurrence (RR = 10.526, P = 0.033; RR = 24.97, P = 0.008) in multivariate analysis. Cholecystectomy was not a protective factor against recurrence of cholangitis (P = 0.615).Conclusions: Angulation of the CBD (≤ 130°) and RHD (≤ 125°) on ERCP are independent risk factors for recurrent cholangitis. Further prospective studies using these data may be warranted for a more accurate estimation and verification of the risk factors predisposing to recurrent cholangitis.